OFFICIAL MEDICATIONS FOR ANTI-TUMOR GENE THERAPY - E. R. Nemtsova; O. A. Bezborodova; R. I. Yakubovskaya; A. D. Kaprin (Исследования и практика в медицине)
This is a review of modern literature data of official medications for anti-tumor gene therapy as well as of medications that finished clinical trials.The article discusses the concept of gene therapy, the statistical analysis results of initiated clinical trials of gene products, the most actively developing directions of anticancer gene therapy, and the characteristics of anti-tumor gene medications.Various delivery systems for gene material are being examined, including viruses that are defective in  replication (Gendicine™ and Advexin) and oncolytic (tumor specific conditionally replicating) viruses (Oncorine™, ONYX-015, Imlygic®).By now three preparations for intra-tumor injection have been introduced into oncology clinical practice: two of them – Gendicine™ and Oncorine™ have been registered in China, and one of them – Imlygic® has been registered in the USA. Gendicine™ and Oncorine™ are based on the wild type p53 gene and are designed for treatment of patients with head and neck malignancies. Replicating adenovirus is the delivery system in Gendicine™, whereas oncolytic adenovirus is the vector for gene material in Oncorine™. Imlygic® is based on the  recombinant replicating HSV1 virus with an introduced GM–CSF gene and is designed for treatment of  melanoma patients. These medications are well tolerated and do not cause any serious adverse events. Gendicine™ and Oncorine™ are not effective in monotherapy but demonstrate pronounced synergism with chemoand radiation therapy. Imlygic® has just started the post marketing trials.